High-Performance Work System and Employee Performance: Case Study at Koja Container Terminal - PRANOGYO, ANTAIWAN BOWO; LUDDIN, MUCHLIS R.; SUYATNO, THOMAS (The journal of contemporary issues in business and government, 2021)
Container Terminal (TPK) Koja is a terminal intended for loading and unloading activities of goods, especially containers. Good employee performance will affect the quality of the process and loading and unloading services produced. This research is qualitative research with case studies on TPK Koja. The purpose of the research was to find out if a high-performance work system (HPWS) is good to be applied in TPK Koja and how HPWS role to the performance of TPK Koja employees. Calculate the weight of each KPI using the Analytical Hierarchy Process method and measure the value of performance achievement by scoring system method and evaluate performance measurement results with Traffic Light System. The results of the study showed HPWS had a positive impact on employee performance and the measurement results showed 15 HPWS KPIs were at the green level or within the specified target.